Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine which quadratic equation is equivalent to [tex]\((x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0\)[/tex], let's perform a substitution step-by-step.
1. Identify a substitution variable [tex]\(u\)[/tex]:
Let [tex]\(u\)[/tex] be a substitution for [tex]\(x^2 - 1\)[/tex]. This gives us:
[tex]\[ u = x^2 - 1 \][/tex]
2. Substitute [tex]\(u\)[/tex] into the original equation:
Replace every occurrence of [tex]\(x^2 - 1\)[/tex] in the equation with [tex]\(u\)[/tex]:
[tex]\[ (x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0 \][/tex]
Substituting [tex]\(x^2 - 1 = u\)[/tex]:
[tex]\[ u^2 - 11u + 24 = 0 \][/tex]
3. Compare the obtained equation to the given options:
From the substitution, the equation simplifies to:
[tex]\[ u^2 - 11u + 24 = 0 \][/tex]
where [tex]\(u = x^2 - 1\)[/tex].
Now, let's see which option matches this derived equation:
- Option 1: [tex]\(u^2 - 11u + 24 = 0\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 2: [tex]\((u^2)^2 - 11(u^2) + 24\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 3: [tex]\(u^2 + 1 - 11u + 24 = 0\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 4: [tex]\((u^2 - 1)^2 - 11(u^2 - 1) + 24\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
Clearly, the first option matches our derived equation. Therefore, the correct quadratic equation equivalent to [tex]\((x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0\)[/tex] is:
[tex]\[ u^2 - 11u + 24 = 0 \; \text{where} \; u = x^2 - 1 \][/tex]
1. Identify a substitution variable [tex]\(u\)[/tex]:
Let [tex]\(u\)[/tex] be a substitution for [tex]\(x^2 - 1\)[/tex]. This gives us:
[tex]\[ u = x^2 - 1 \][/tex]
2. Substitute [tex]\(u\)[/tex] into the original equation:
Replace every occurrence of [tex]\(x^2 - 1\)[/tex] in the equation with [tex]\(u\)[/tex]:
[tex]\[ (x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0 \][/tex]
Substituting [tex]\(x^2 - 1 = u\)[/tex]:
[tex]\[ u^2 - 11u + 24 = 0 \][/tex]
3. Compare the obtained equation to the given options:
From the substitution, the equation simplifies to:
[tex]\[ u^2 - 11u + 24 = 0 \][/tex]
where [tex]\(u = x^2 - 1\)[/tex].
Now, let's see which option matches this derived equation:
- Option 1: [tex]\(u^2 - 11u + 24 = 0\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 2: [tex]\((u^2)^2 - 11(u^2) + 24\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 3: [tex]\(u^2 + 1 - 11u + 24 = 0\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
- Option 4: [tex]\((u^2 - 1)^2 - 11(u^2 - 1) + 24\)[/tex] where [tex]\(u = x^2 - 1\)[/tex]
Clearly, the first option matches our derived equation. Therefore, the correct quadratic equation equivalent to [tex]\((x^2 - 1)^2 - 11(x^2 - 1) + 24 = 0\)[/tex] is:
[tex]\[ u^2 - 11u + 24 = 0 \; \text{where} \; u = x^2 - 1 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.